The case of acute psychotic episode treatment in patient with myasthenia gravis - Patrycja Pajor; Maria Jankowska; Marek Jarema (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
A seventy-one old male patient with no previous Hx of mental disorders including alcohol use and with no family Hx of mental disorders was admitted to psychiatric ward due to acute aggression, agitation, excessive irritability and lack olf sleep. He suferred from myasthenia gravis for years and was treated chronically with ambenonium 20 mg daily. Because of comorbidity of uveitis with macular edema he received treatment with prednisolone 70mg daily. Because of acute psychotic symptoms the treatment with olanzapine up to 20mg/d was introduced without effect. The treatment was switched to haloperidol 10mg/d with gradual improvement of patient's behaviour. He was discharged from the hospital with indication to continue psychiatric, ohpthalomogic, and neurological outpatient care.